Blood Rites - Butcher, Jim (New York : Roc, 2004)
While going undercover on the set of an adult film to investigate the mysterious deaths of several actresses, Chicago wizard Harry Desden unexpectedly learns the shocking truth about his vampire friend Thomas.
Keywords: Dresden, Harry (Fictitious character); Wizards -- Illinois -- Chicago; Fantasy fiction, American; Mystery and detective stories; Fantasy fiction